2019
DOI: 10.1115/1.4044032
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Articular Cartilage Focal Defect Size and Location in Whole Knee Biomechanics Models

Abstract: Articular cartilage focal defects are common soft tissue injuries potentially linked to osteoarthritis (OA) development. Although several defect characteristics likely contribute to osteoarthritis, their relationship to local tissue deformation remains unclear. Using finite element models with various femoral cartilage geometries, we explore how defects change cartilage deformation and joint kinematics assuming loading representative of the maximum joint compression during the stance phase of gait. We show how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…10 Compressive strains can increase between 50 and 100%, depending on defect size and location. 11 Regardless of location of the defect within the joint, the general cascade of events follows a similar pathway of cell phenotype alterations, necrosis, and/or apoptosis; proteoglycan and collagen disruption, alteration and loss; inflammation; degradation; and remodeling regardless of etiology. However, the timing, order, and severity of responses can vary greatly.…”
Section: The Spectrum Of Pathologymentioning
confidence: 99%
“…10 Compressive strains can increase between 50 and 100%, depending on defect size and location. 11 Regardless of location of the defect within the joint, the general cascade of events follows a similar pathway of cell phenotype alterations, necrosis, and/or apoptosis; proteoglycan and collagen disruption, alteration and loss; inflammation; degradation; and remodeling regardless of etiology. However, the timing, order, and severity of responses can vary greatly.…”
Section: The Spectrum Of Pathologymentioning
confidence: 99%
“…9 The increase in local mechanical stress near the edge of the defect area may herald a potential mechanical overload of cells near the damaged tissue. 10 Conventional biomechanical experiments insufficiently shed light on the biomechanical features of articular cartilage to assist clinical treatment. 11 Hunt et al's experimental study 9 using cadaveric ankle joints found a high-stress presence near the rim of defect cartilages when the defect sizes reached 10 mm and above.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies were conducted on the articular cartilage behavior with multiple constitutive models, 3742 the mechanical response of heterogeneous cartilage at maximum loading position in a gait is not adequately compared. Therefore, our primary objective is to address this issue by considering graded cartilage material with multiple heterogeneous constitutive models.…”
Section: Introductionmentioning
confidence: 99%
“…33 The highly heterogeneous nature of superficial zone can simulate well with such models 34,35 the most influential compartment on articular cartilage to mechanical response. 36 Although many studies were conducted on the articular cartilage behavior with multiple constitutive models, [37][38][39][40][41][42] the mechanical response of heterogeneous cartilage at maximum loading position in a gait is not adequately compared. Therefore, our primary objective is to address this issue by considering graded cartilage material with multiple heterogeneous constitutive models.…”
Section: Introductionmentioning
confidence: 99%